Learning interest and discipline on the motorcycle business engineering student learning outcomes - Alfischo, Febrian (Research in Education and Technology (REGY), 2024)
This research aimed to analyze the relationship between learning interest and discipline on the learning outcomes of 11th-grade Motorcycle Business Engineering students at SMK Negeri 1 Sintuk Toboh Gadang. A quantitative correlational research method was used with all 11th-grade Motorcycle Business Engineering students as subjects. Data collection techniques used questionnaires to measure learning interest and discipline, and documentation for learning outcome data. Data analysis used the product-moment correlation test. Results showed no significant relationship between learning interest or learning discipline and learning outcomes. However, a strong positive correlation was found between learning interest and discipline. Most students demonstrated moderate to good learning interest and discipline levels, with satisfactory learning outcomes. In conclusion, although students’ learning interests and discipline were fairly good, this was not reflected in their learning outcomes, indicating the need for further research on other factors influencing vocational high school students’ learning outcomes.